Correction: Huang et al. Identification of the Novel Tumor Suppressor Role of FOCAD/miR-491-5p to Inhibit Cancer Stemness, Drug Resistance and Metastasis via Regulating RABIF/MMP Signaling in Triple Negative Breast Cancer. Cells 2021, 10, 2524 - Wei-Chieh Huang; Hsiang-Cheng Chi; Shiao-Lin Tung; Po-Ming Chen; Ya-Chi Shih; Yi-Ching Huang; Pei-Yi Chu (Cells)
In the original publication [...]